Etnomatemática de la carpintería y la costura: una estrategia para el fortalecimiento del pensamiento geométrico y espacial en grado séptimo (2022)
In this degree word, a didactic proposal is presented to strengthen the development of geometric and spatial thinking in seventh grade students, from the ethnomathematics found in the carpentry and sewing trades and starting from Project Based Learning - PBL. A didactic sequence was carried out for the creation of elaborate materials (products) with wood and fabric in which western knowledge of mathematics was covered, such as: scale factor, polygons, angles, geometric transformations, polyhedrons and calculation of area and volume. The implementation of the didactic material was carried out at the Colegio Distrital Paulo Freire in the morning with thirty eight students of grade 701 in person, during ten sessions of an hour and a half each, which is systematized and analyzed qualitatively. It is concluded that the ethnomathematics present in the carpentry and sewing trades contributes to the development of geometric thinking in the PBL in a group way, however, it is important to implement it in a longer time so that the necessary indications in the development can be given of individual tasks.